Experiences of community-dwelling older adults with chronic low back pain in Hong Kong and Switzerland – A qualitative study - Schoeb, Veronika; Misteli, Marceau; Kwan, Crystal; Wong, Chris W. Y.; Kan, Mandy M. P.; Opsommer, Emmanuelle; Wong, Arnold Y. L. (Frontiers in Rehabilitation Sciences, 2022)
Introduction The prevalence of chronic low back pain (LBP) increases with age and older adults are more vulnerable to develop chronic LBP. A recent Swiss study has shown that 78% of community-dwelling older adults aged ≥65 years experienced chronic LBP. Similarly, a study in Hong Kong found that approximately 30% of people aged above 60 years experienced chronic LBP. The aim of this collaborative research project was to illuminate older adults' experiences of living with chronic LBP and its implication on older adults' daily life in Western and Eastern cultures. Methods Twenty-five older people experiencing chronic LBP living in Switzerland or Hong Kong were recruited through health professionals or community centres. Using semi-structured interviews, participants shared their experiences regarding chronic LBP and its implications on their daily life. The interviews were recorded and transcribed “ad verbatim” in the original language. An inductive thematic analysis was used, using a qualitative data analysis software program (NVivo) and a shared code book in English. The Swiss and Hong Kong research teams engaged in collaborative analysis until a consensus was established, taking into consideration of cultural specificities. Ethical approval was obtained from the local ethic committees in both regions. Results Themes were related to negative perceptions/experiences: (1) interferences of daily function; (2) pessimistic attitudes toward their conditions/prognosis; and (3) self-perceived burden related to families. Conversely, four themes revealed attributes to social roles: (1) maintaining their roles in families; (2) experiencing supports from family and friends; (3) being content despite LBP; and (4) enjoying social activities. Cultural differences between Switzerland and Hong Kong were related to social circles and offers from the healthcare system, influencing individual experiences and perceptions. Discussion Although chronic LBP may negatively impact older adults, individual approaches as well as social and health system supports influence older adults' attitude toward their pain and self-management strategies. Developing effective and culturally sensitive interventions for an elderly population with chronic LBP can be challenging but essential for the development of innovative healthcare services tailored to the population's needs. The methodological approach used for this research project establishes the framework for developing and evaluating complex interventions.